Inhibition of the glucose induced insulin release by somatostatin in the isolated perfused rat pancreas. Action of cyclic AMP, glucagon and glibenclamide (Revista Española de Fisiología, 1976)
Insulin release in the perfused isolated rat pancreas was measured after stimulation with 16.5 mM glucose with and without somatostatin (cycle form, 100 ng/ml) in the medium. A complete blockage of the typical biphasic pattern of insulin release ocurred with somatostatin in the medium. Such blockage was abolished when cAMP (2.5 mM) and a 0.5 ml solution of glucagon (1 mg/ml) were continuously perfused for 20-minute periods and for 30-second periods correspondently. It did not take place when glibenclamide (HB-419) was perfused for a 20-minute period at a rate of 10 mug/ml. The results suggest that the adenylcyclase dependent mechanisms of glucose-induced insulin release are involved in the inhibition of the glucose-induced insulin secretion by somatostatin.